Strategija pospeševanja slovenskih neposrednih investicij v tujino - Svetličič, Marjan (Teorija in praksa, 2000)
An increasing share of world exports is linked to the establishment of companies abroad. Therefore, corporate sector of a small Slovenia's economy/market, which is crucially dependent on foreign markets, should not avoid investing abroad. One of important tasks of the Slovenian government in the future is to create adequate conditions which would help Slovenian companies to internationalise their activities. We are in favour of active promotion of the internationalisation of activities of Slovenian companies, in the first place of promotion of outward FDI which would speed up the restructuring of Slovenian economy and individual companies. If one follows the opinion of existing Slovenian investors abroad, the state could help them in the following way, that is with the following measures: (i) collection and disseminatrion of information on the opportunities for investing in projects abroad, (ii) establishing initial contacts with potential foreign partners, (iii) improvement of Slovenian climate and regulatory framework for outward FDI, (iv) co-financing of certain activities related with projects of investing abroad, (v) co-financing of equity and/or improving access (conditions) to commercial sources of finance, (vi) assistance in training of skills, necessary when investing abroad, (vii) insurance of outward FDI projects and, thus, reduction of risk, (viii) lobbying for improvement of investing conditions in host countries, (ix) more assistance of Slovenia's diplomatic representatives abroad to Slovenian investors in general.
Keywords: Slovenia; Slovenija; investicije; direktne investicije; tuje investicije; strategija; ekonomski razvoj